SLC22A2 gene 808 G/T variant is related to plasma lactate concentration in Chinese type 2 diabetics treated with metformin - Li Qing; Liu Fang; Zheng Tai-shan; Tang Jun-ling; Lu Hui-juan; Jia Wei-ping (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the potential relationship between the SLC22A2 gene polymorphism and blood lactate concentration in Shanghai Hans suffering from type 2 diabetes mellitus (T2DM). Methods: The SLC22A2 single nucleotide polymorphism (SNP) 808G/T was genotyped in 400 T2DM patients, including a metformintreated group (n=200) and a non-metformin-treated group (n=200). Fasting plasma lactic acid levels were measured with an enzymeelectrode assay. Biochemical indexes, including plasma alanine aminotransferase (ALT), creatinine (Cr), and glycolated hemoglobin (HbA1c), were also measured. Results: The fasting plasma lactate concentration in the metformin-treated group was significantly higher than that in the non-metformin-treated group (1.29±0.45 mmol/L vs 1.18±0.44 mmol/L, P=0.015). Additionally, the ratio of patients with hyperlactacidemia was 8% (16/200) for the metformin-treated group and 5.5% (11/200) for the non-metformin-treated group, with no lactic acidosis found in either group. The frequency of the SLC22A2 808G/T T allele was 12.9%. Patients with the mutant genotype (TT) had a higher blood lactate concentration in the metformin-treated group than those in the non-metformin-treated group (t=2.492, P=0.013). This trend was not observed in the GG and GT genotypes when compared with metformin-treated and non-metformin-treated groups. Patients with the mutant genotype (TT) in the metformin-treated group also had a higher incidence of hyperlactacidemia compared with the GG genotype (40.0% vs 6.9%, P=0.050) in the metformin-treated group and the GG (6.0%, P=0.042) or GT (4.3%, P=0.043) genotypes in the non-metformin-treated group. In the metformin-treated group, there were significant gender differences in lactate concentrations in the TT (2.18±0.15 vs 1.04±0.27 mmol/L, P=0.008) and GG genotypes (1.40±0.51 vs 1.19±0.35 mmol/L, P=0.004). The lactate levels of women with the TT genotype were the highest in the metformin-treated group, but differences in lactate levels among the genotypes were not observed in the non-metformin-treated group. Conclusion: There is an 808G/T polymorphism in the SLC22A2 gene in Chinese Hans with T2DM. The 808G>T variance in the SLC22A2 gene can affect the plasma lactate level and the incidence of hyperlactacidemia in T2DM patients undergoing metformin therapy. Additionally, the female patients carrying the TT genotype are prone to lactatemia.